Attachment Insecurity and Psychological Flexibility in Emergent Adulthood: The Mediating Role of Self-Compassion - OLARU, Ionela-Vasilica-Andreea; COSTEA-BĂRLUȚIU, Carmen (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
Attachment is a crucial component of development throughout life and attachment security is a resilience factor, contributing to adjustment to life challenges, as well as educational context. The current research aims to approach attachment dimensions, in relation to psychological flexibility and inflexibility and self-compassion, investigating a mediation model of self-compassion in the relationship between attachment avoidance and anxiety dimensions and psychological flexibility. The research also aims to collect data on the complex relationships between the three aforementioned constructs and their components, global self-compassion and its components, anxious and avoidant attachment. The research included 50 participants, a population of college students, who agreed to complete measures of anxiety and avoidance in attachment relationships, self-compassion, and psychological flexibility and inflexibility. Our results indicate significant correlations between attachment anxiety, self-compassion, and psychological flexibility and inflexibility. Two total mediation effects were found in the association between the attachment anxiety dimension and self as context and the attachment anxiety dimension and fusion, relationships mediated by self-compassion. Our results will be discussed in the light of the needs of emergent adults, in terms of both mental health and guidance towards healthy development in emergent adulthood.